Review on the prevalence and economic importance of camel tuberculosis in Ethiopia - Merga Firdisa Duguma (Journal of Food Science and Nutrition Therapy - Peertechz Publications, 2022)
Camel tuberculosis is a chronic disease, which is portrayed by the development of granulomas, essentially in the respiratory tract and related lymph nodes, from which the mycobacteria are discharged and contaminate other susceptible animals. Camel tuberculosis has public health implications, especially in pastoral areas of Ethiopia due to the communities having the habit of consuming raw milk and its products and those who do have consistent or day-to-day contact with their camels. In the pastoral areas of Ethiopia, the camel is the spine of their everyday life and extraordinarily adjusted to cruel conditions camels are for the most part raised in Afar, Somali, and Oromia (Borena, Kereyu and Guji). Camels have a high contribution to the economic development of the country. The pastoral community utilized camel products, such as milk and meat, and used camels for various purposes for example, for transportation, drafting, ploughing land, festivity and rivalry as in dashing. In most parts of Ethiopia, camel milk is accepted as a treatment for gastritis, asthmatics, stomach inconvenience, HIV, Hamot (kar), tuberculosis, fever, urinary issues and hepatitis. Among significant illnesses, tuberculosis is one of the principles, which influence camel's Health and has a zoonotic impact. In addition to this, the etiological agents are transmitted to humans through an aerogenous route from those animals with active cases in the herd. The infection has been reported from several parts of pastoral areas of the country essentially dependent on tuberculin tests and abattoir inspections. Therefore, attention should be given to the control of tuberculosis in livestock; public health education on the zoonotic importance of the disease or awareness creation and the national tuberculosis control needs to consider the one health approach and further epidemiological studies should be undertaken.